2018
DOI: 10.1177/1357633x18805661
|View full text |Cite
|
Sign up to set email alerts
|

Ideal telestroke time targets: Telestroke-based treatment times in the United States stroke belt

Abstract: Background Studying critical time interval requirements can enhance thrombolytic treatment for stroke patients in telestroke networks. We retrospectively examined 12 concurrent months of targeted time interval information in the South Central US telemedicine programme, Arkansas Stroke Assistance through Virtual Emergency Support (AR SAVES). Hypothesis: We hypothesised that consult data analysis would highlight areas for improvement to shorten overall door to Intra venous (IV) tissue plasminogen activator (tPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This is a continued impediment for IV tPA administration. 6,28,29,33 Several strategies including pre-hospital notification, [34][35][36] utilization of modified stroke scales for paramedics, 37,38 setting up of telestroke units in rural areas 14,23,39 and public stroke education have been employed to tackle this problem. However, late presentation still is one the most common factors limiting the eligibility for IV tPA in stroke patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a continued impediment for IV tPA administration. 6,28,29,33 Several strategies including pre-hospital notification, [34][35][36] utilization of modified stroke scales for paramedics, 37,38 setting up of telestroke units in rural areas 14,23,39 and public stroke education have been employed to tackle this problem. However, late presentation still is one the most common factors limiting the eligibility for IV tPA in stroke patients.…”
Section: Resultsmentioning
confidence: 99%
“…12 Telestroke practice has led to significant improvement in stroke care around the world [13][14][15][16][17][18][19][20] with evolving guidelines for telestroke practice. [21][22][23] Given the improvement in stroke care by telestroke networks, we wanted to explore the most common reasons for not getting IV tPA in telestroke care, which might be useful to improve treatment rates in future.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose was to improve transport times to medical facilities qualified for stroke care and, as a result, to decrease time to treat. Two primary arms of the program are (1) development of telestroke centers in rural hospitals and (2) provision of information on qualified stroke centers to emergency services paramedics transporting patients [21][22][23]. Its success is reflected in the approximately 2000 patients treated, a treatment rate increase of >30%, and improved transport times to qualified stroke centers [21,24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that D-NC and Con play a major role in DTN [90]. Various factors including, when the consultant is notified, the time a consultant takes to interview the patient, and the experience level of the staff aiding with the examination will have to be considered while analyzing such data.…”
Section: Process Measuresmentioning
confidence: 99%